2010
DOI: 10.1371/journal.pntd.0000756
|View full text |Cite
|
Sign up to set email alerts
|

A Tractable Experimental Model for Study of Human and Animal Scabies

Abstract: BackgroundScabies is a parasitic skin infestation caused by the burrowing mite Sarcoptes scabiei. It is common worldwide and spreads rapidly under crowded conditions, such as those found in socially disadvantaged communities of Indigenous populations and in developing countries. Pruritic scabies lesions facilitate opportunistic bacterial infections, particularly Group A streptococci. Streptococcal infections cause significant sequelae and the increased community streptococcal burden has led to extreme levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 42 publications
(58 reference statements)
3
78
0
Order By: Relevance
“…This includes studies on wound healing (Ansell et al, 2012;Jung et al, 2013;Sullivan et al, 2001), burns (Abdullahi et al, 2014;Sheu et al, 2014), transdermal penetration, delivery and toxicology (Barbero and Frasch, 2009;Godin and Touitou, 2007;Mahl et al, 2006;Simon and Maibach, 2000;Yu et al, 2013), infectious diseases (Mounsey et al, 2010;Rampton et al, 2013;San Mateo et al, 1999), radiation and UVB impact (Agay et al, 2010;Brozyna et al, 2009;Smirnova et al, 2014), snake venom (Imkhieo et al, 2009) and taser (Jenkins et al, 2013) assessments, as well as stem cell research (Hao et al, 2009;Zhao et al, 2012). The pig was also employed as a model for experimentally induced allergic contact dermatitis, revealing similarities to human with respect to clinical, histological and immunohistological features (Vana and Meingassner, 2000).…”
Section: Skin Structure and Advantages Of The Pig Modelmentioning
confidence: 99%
“…This includes studies on wound healing (Ansell et al, 2012;Jung et al, 2013;Sullivan et al, 2001), burns (Abdullahi et al, 2014;Sheu et al, 2014), transdermal penetration, delivery and toxicology (Barbero and Frasch, 2009;Godin and Touitou, 2007;Mahl et al, 2006;Simon and Maibach, 2000;Yu et al, 2013), infectious diseases (Mounsey et al, 2010;Rampton et al, 2013;San Mateo et al, 1999), radiation and UVB impact (Agay et al, 2010;Brozyna et al, 2009;Smirnova et al, 2014), snake venom (Imkhieo et al, 2009) and taser (Jenkins et al, 2013) assessments, as well as stem cell research (Hao et al, 2009;Zhao et al, 2012). The pig was also employed as a model for experimentally induced allergic contact dermatitis, revealing similarities to human with respect to clinical, histological and immunohistological features (Vana and Meingassner, 2000).…”
Section: Skin Structure and Advantages Of The Pig Modelmentioning
confidence: 99%
“…Animal models provide the opportunity to investigate the immunopathologic mechanisms of scabies development, and a tractable porcine model of scabies has been recently developed (11,16). When infested with S. scabiei var.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood responses were compared at early (1 week) and late (15 weeks) stages of scabies mite infestation, with local skin responses also examined at 15 weeks post-infestation. It has been suggested that IL-17 secretion by CD3 + cd + T cells plays a critical role in the pathogenesis of skin chronic inflammation, such as psoriasis (16)(17)(18). As some of the clinical manifestations of crusted scabies, such as epidermal hyperproliferation, are similar to psoriasis, we also investigated whether the levels of IL-17 were increased in mite-infested pigs, especially those with crusted scabies.…”
Section: Introductionmentioning
confidence: 99%
“…Scabies mites in this colony were originally obtained from naturally infested pigs and have had no known acaricide exposure. Establishment of this model and protocols for mite collection have been described in detail previously (23). Briefly, skin scrapings were obtained from the ears of infested pigs and transported to the laboratory.…”
mentioning
confidence: 99%